2012
DOI: 10.1016/j.jcin.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Walking Beyond the GRACE (Global Registry of Acute Coronary Events) Model in the Death Risk Stratification During Hospitalization in Patients With Acute Coronary Syndrome

Abstract: Despite having been developed over 8 years ago, the GRACE RS still maintains its excellent performance for predicting in-hospital risk of death among ACS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
1
18
0
5
Order By: Relevance
“…The GRACE score is more accurate in predicting long-term mortality for myocardial infarction patients in China. 8,9 A recent study by Cinar et al (2019) showed that the results of his research support our study. Their study aims to evaluate the use of simple risk index score with TIMI Index (TRI) score to predict stent thrombosis (ST) in STEMI patients who underwent percutaneous primary coronary intervention (PCI).…”
Section: Discussionsupporting
confidence: 90%
“…The GRACE score is more accurate in predicting long-term mortality for myocardial infarction patients in China. 8,9 A recent study by Cinar et al (2019) showed that the results of his research support our study. Their study aims to evaluate the use of simple risk index score with TIMI Index (TRI) score to predict stent thrombosis (ST) in STEMI patients who underwent percutaneous primary coronary intervention (PCI).…”
Section: Discussionsupporting
confidence: 90%
“…Then, patient charts were retrieved and collected from record and documentation office. Data were collected by developing a data abstraction format which was prepared using global registry of acute coronary events (GRACE) as well as incorporating studies from India and European countries [16][17][18][19][20][21]. Four trained clinical pharmacists who had good experience in the clinical practice were recruited for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…In patients with STEMI, previous MI, door to balloon time, the presence of diabetes, anemia, chronic renal failure, and ejection fraction on admission are the main predictors of mortality. Risk scores such as TIMI, GRACE, PAMI, Zwolle, or CADILLAC are commonly applied as mortality indicators (3)(4)(5)(6)13,14). Beyond clinical data, angiographic data are also used to predict the longterm prognosis, such as the SYNTAX score (15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, risk stratification is essential for clinical decision and management. Various risk scores such as Thrombolysis in Myocardial Infarction (TIMI), GRACE, and ZWOLLE have been applied (3)(4)(5). Besides angiographic variables, clinical data, such as the presence of anemia and renal impairment, are independent risk factors for in-hospital cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%